Studi Komparasi Konstitutif Model untuk Kasus Galian Dalam dengan Metoda Elemen Hingga dan Data Monitoring Lapangan: Studi Kasus Proyek Muara Karang - Jwantoro, Jwantoro; Susila, Endra; Apoji, Dayu; Basarah, Yuammar Immarazan (Jurnal Teknik Sipil, 2025)
The construction of underground structures at the Muara Tawar Combined Cycle Power Plant, situated in a coastal area characterized by very soft clay soils, presents significant geotechnical challenges. Careful analysis and planning are crucial to prevent structural failure. This study evaluates the effectiveness of temporary retaining wall systems using sheet piles and strutting during the excavation of the Steam Turbine Generator (STG) Block #4 basement, which is adjacent to existing structures. Utilizing PLAXIS 2D, an advanced Finite Element Method (FEM) software for geotechnical analysis, we modeled and analyzed the soil-structure interaction to optimize the design and construction methodology. The study focused on determining appropriate support systems for deep excavation, ensuring the stability of both the new construction and existing facilities. Results demonstrate that the proposed sheet pile and strutting system effectively prevents soil collapse during construction. This is evidenced by satisfactory safety factors and acceptable deflection values derived from numerical analyses. This research was conducted by comparing three soil models: Mohr-Coulomb, Soft Soil, and Hardening Soil, to analyze their performance in predicting soil behavior for construction purposes.